Effects of increasing honeybee densities on sunflower yield components - Reyes, María Fernanda (2024)
The management of domesticated honeybees (Apis mellifera) could be a useful tool to supplement wild pollinators and increase crop productivity. However, is necessary to know the optimal hive density for each particular crop. Sunflower (Helianthus annuss) is the third most produced oilseed crop in the world, and depends on insect pollination to increase the number of seeds and the oil content. We proposed to quantify the H. annuss dependency to pollinators and assess the optimal hive density of honeybees to increase sunflower productivity in 2 ha plots immerses in an extensive soybean matrix in Argentina. We set up a field experiment of five plots with a different number of hives each one (0, 5, 10, 15, 20), assessed fruit set and crop yield of flower heads open and20 excluded from pollinators and insect abundance. Fruit set and crop yield increased in open flower heads. Crop yield did not present a linear response to hive density, although there could be a positive effect of intermediate densities. Crop yield were no explained by abundance of the two most frequently pollinator species, Astylus atromaculatus (Coleoptera) and Apis mellifera, suggesting that23 sunflower productivity was limited by other resources than pollen, as low abundance of rains. Drought conditions could have limited the response of the crop to hive addition and also influenced the high A. atromaculatus abundance, which could play a pollinator role in this system. More repetitions (plots and years) are needed to get these results more robust.